Protein phosphorylation and the control of protein synthesis - Proud, Christopher (Henry Stewart Talks, 2010)
Protein synthesis, Key step in gene expression that must be tightly controlled, Signaling pathways regulate phosphorylation and activity of translation factor proteins, Important in regulation of cell growth and division, Defective control linked to human diseases such as cancer and cardiac hypertrophy